2004
DOI: 10.1021/jm030974c
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial and Antitumor Evaluation of Novel C-10 Non-Acetal Dimers of 10β-(2-Hydroxyethyl)deoxoartemisinin

Abstract: Four series of C-10 non-acetal dimers were prepared from key trioxane alcohol 10beta-(2-hydroxyethyl)deoxoartemisinin (9b). All of the dimers prepared displayed potent low nanomolar antimalarial activity versus the K1 and HB3 strains of Plasmodium falciparum. The most potent compound assayed was phosphate dimer 14a, which was greater than 50 times more potent than the parent drug artemisinin and about 15 times more potent than the clinically used acetal artemether. In contrast to their potent activity versus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 36 publications
2
68
0
Order By: Relevance
“…These drugs are widely used, with over 100 million courses administered annually (54), despite the fact that embryotoxicity in rats and rabbits (55,56) and in vivo and in vitro neurotoxicity (57, 58) have been reported. Artemisinins can display cytotoxic activity in actively proliferating mammalian cells (5)(6)(7)(8)(9)(10)(11)(12), and it is suggested that toxicity is related to high intracellular iron concentrations (15,16,18). It is therefore essential that the chemical and molecular mechanisms of endoperoxide cytotoxicity are defined to assess the safe and effective use of this class of drugs in the established area of malaria and their potential use in the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs are widely used, with over 100 million courses administered annually (54), despite the fact that embryotoxicity in rats and rabbits (55,56) and in vivo and in vitro neurotoxicity (57, 58) have been reported. Artemisinins can display cytotoxic activity in actively proliferating mammalian cells (5)(6)(7)(8)(9)(10)(11)(12), and it is suggested that toxicity is related to high intracellular iron concentrations (15,16,18). It is therefore essential that the chemical and molecular mechanisms of endoperoxide cytotoxicity are defined to assess the safe and effective use of this class of drugs in the established area of malaria and their potential use in the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For the dimers, linkages with one amideor one sulfur centered two ethylene groups are essential for high anticancer activity. Antitumor activity of deoxoartemisinin dimers has also been studied by Jeyadevan et al [106] and Posner et al [107]. Cho et al [108] synthesized 10-substitured triazolylartemisinin compounds and tested them on various cancer cell lines (human colorectal adenocarcinoma, human glioma, human cervical carcinoma and mouse melanoma).…”
Section: Other Monomers and Artemisinin Hybridsmentioning
confidence: 98%
“…90 The potential drawback of these dimers is the presence of metabolically unstable C-10 acetal linkage. Jeyadevan et al 91 and O'Neill et al 92 have recently reported antimalarial and antitumor activities of some non-acetal C-10 carba dimers and two most potent derivatives were 8 and 9 (see Fig. 3).…”
Section: A Artemisinin and Its Derivativesmentioning
confidence: 92%
“…Derivative 8 displayed about 62-fold increase in antimalarial activity with IC 50 value of 0.3 nM against K1 strain. 91 The isobutyric acid dimeric analog 9, on the other hand upon single dose ip administration to mice was found to be safe and displayed a therapeutic index six times that of sodium artesunate. 92 It is commonly known that acetal-type DHA derivatives undergo a facile hydrolysis under the acidic conditions in addition to enzymatic oxidation resulting in the formation of DHA.…”
Section: A Artemisinin and Its Derivativesmentioning
confidence: 99%